Dodd-frank implementation update: key differences between the CFTC and SEC final business conduct standards and related cross-border requirements. Issue 3 (5th September 2016) - Architzel, Paul M.; Berkovitz, Dan M.; Bernstein, Gail; Davis, Seth; Serafini, Ted
Abstract : Purpose: To analyze the differences between the SEC's newly adopted final business conduct rules for security-based swap dealers and major security-based swap participants under Section 15F(h) of the Securities Exchange Act of 1934 and the parallel rules promulgated under the Commodity Exchange Act by the CFTC with respect to swap dealers and major swap participants. Design/methodology/approach: This article discusses select rules under each regulatory regime and highlights the major differences and potential effects of each. Findings: This article concludes that while the SEC's intent was to harmonize its final rules with the parallel CFTC rules, there are substantive differences between the two sets of rules that firms should consider when deciding how to structure their security-based swap dealer activities. Originality/value: This article contains insightful analysis of the newly adopted SEC Business Conduct Rules and highlights some of the ways firms will likely be affected moving forward.